The Profile of Students’ Analytical Thinking Skills on Chemistry Systemic Learning Approach - Nur Fitriyana; Marfuatun Marfuatun; Erfan Priyambodo (Scientiae Educatia: Jurnal Pendidikan Sains, 2019)
The movement of educational systems on the 21st century need to be change from linearity to systemic form. The aims of this research is to determine the effect of Chemistry Systemic Learning Approach (CSLA) toward Students’ Analytical Thinking Skills (SATS). A pre-experimental with pre-test and post-test design was adopted in this research. The population of this study were all of the students of public senior high school in Kulon Progo regency, Yogyakarta, Indonesia. Two classes from a public senior high school in those regency were cluster randomly selected as the research samples. A Systemic Test on Analytical Thinking (STAT) was used to collect the data of SATS, before and after the implementation of CSLA. The STAT covering four indicators of analytical thinking, they are differentiating, organizing, and attributing indicators. Meanwhile, the CSLA was integrated in the teaching-learning process and in the STAT, the CSLA was presented in the form of cyclic diagrams. The data of SATS on CSLA were analyse according to paired samples t-test and n-gain category analysis. The results of these analysis indicates that there was significant effect of CSLA on SATS. Moreover, the profile of SATS shows a satisfied improvement after the implementation of CSLA. Overall, a high n-gain category was reached that indicates the enhancement of students’ understanding of the inter-related concept in chemistry. This study gives a significant contribution on the use of CSLA to improve SATS. Hence, the used of CSLA should be emphasized on chemistry learning to promote students’ higher order thinking skills.